Processing Non-at-Issue Meanings of Conditional Connectives: The wenn/falls Contrast in German - Liu, Mingya (Frontiers in Psychology, 2021)
Logical connectives in natural language pose challenges to truth-conditional semantics due to pragmatics and gradience in their meaning. This paper reports on a case study of the conditional connectives (CCs) wenn/falls ‘if/when, if/in case’ in German. Using distributional evidence, I argue that wenn and falls differ in lexical pragmatics: They express different degrees of speaker commitment (i.e., credence) towards the modified antecedent proposition at the non-at-issue dimension. This contrast can be modeled using the speaker commitment scale (Giannakidou and Mari, 2016), i.e., More committed